ANALYSIS OF THE POSSIBILITIES OF TEACHING FOLK PEDAGOGY BASED ON MODULAR TECHNOLOGIES (American Journal of Pedagogical and Educational Research, 2025)
This article explores the integration of modular teaching technologies into the instruction of folk pedagogy as a means of enhancing educational quality while preserving national cultural identity. Drawing on qualitative research methods and theoretical frameworks rooted in constructivist and multicultural pedagogy, the study examines how modular systems enable the systematic organization and contextualization of traditional values such as proverbs, rituals, customs, and ethical teachings within formal education. The findings indicate that modularized folk pedagogy fosters learner autonomy, critical thinking, and cultural empathy while offering educators a flexible and effective tool for curriculum development. Moreover, it demonstrates that students engaged in modular folk pedagogy exhibit higher levels of engagement, retention, and behavioral transformation in alignment with traditional moral values. The article concludes with practical recommendations for curriculum designers and policymakers on how to optimize modular frameworks for culturally responsive education.